Investigation of the Effects of Fun Athletics Practices Applied to Primary School Students on Motor Development - Azize ERDOĞAN ÜNAL; Betül BAYAZIT (ümit doğan üstün, 2022)
The present study aimed to examine the contribution of fun athletic activities to the motor development of primary school 1st-grade students. A total of 54 students in two different branches, randomly selected from Defterdar Mehmet Bey Primary School in the Beykoz district of Istanbul participated in the study. The participants were divided into two groups the study and the control group. A fun athletics track consisting of 7 stations was applied to all students. These stations were respectively; The slalom consists of forwarding leaping, ball at wall throwing and catching, ladder crossing, somersault forward, tunnel crossing, and balance. The analysis of the obtained data was made in the SPSS 21.0 package program. Descriptive statistics of the data were calculated. Mann Whitney U and Wilcoxon non-parametric tests were applied. According to the analyzed results, while there was no significant difference between the pre-test and post-test data of the control group, except for the course duration, there was a significant difference between the pre-test and post-test data of the study group, and a significant difference was observed between the post-tests of the control group and the study group in favor of the study group. As a result, it was observed that fun athletics activities made a positive contribution to the motor skills of primary school 1st-grade students.